Tinjauan Yuridis dan Prosedur Penanganan Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial (Studi Implementasi UU ITE No. 1 Tahun 2024) - Anisah, Aura; Nirwana, Rena Putri; Anindya, Salma Elsa; Manogu Sitompul, Theodore Daniel Sebastian; Nugroho, Andriyanto Adhi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to review the legal regulation concerning defamation through social media based on the Information and Electronic Transactions Law (UU ITE) No. 1 of 2024 and to describe the legal procedures for handling defamation crimes via social media. The method used is normative legal research with a juridical and procedural analysis approach. The findings reveal that UU ITE No. 1 of 2024 provides detailed regulation on acts of defamation through social media, including the criminal elements and sanctions imposed, such as imprisonment up to 2 years and a maximum fine of IDR 400 million. The handling procedure typically begins with a complaint from the victim to the authorities, followed by complaint registration, investigation, evidence examination, and if the elements are met, the case proceeds to prosecution and trial stages. In conclusion, the legal provisions in UU ITE offer a strong legal basis to address defamation on social media, and the procedural handling guarantees victim protection and provides a deterrent effect for offenders.